Study of Perceived Constraints Faced By Women Self Help Group Entrepreneurs (Indian Journal of Extension Education, 2014)
The study was conducted in Hathras (now Mahamaya Nagar) district of Uttar Pradesh state (India) in the year 2009-2010. Three blocks viz. Sasni, Hathras and Sikandrarao, consisted the study area. The sample size of the study was 250 self help group members drawn from 50 SHG s by proportionate random sampling technique. The data were collected with the help of a structured interview schedule. From the analysis of constraints, it was concluded that the unfavorable attitude of bank officials¸ dependence on intermediaries and fluctuation of market price were the most serious constraints perceived by the members of SHGs